Internalisasi Nilai-Nilai Pendidikan Agama Islam Dalam Pembinaan Moral Siswa di Sekolah - Biantoro, Oktio Frenki; Rahmatullah, Asep (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2025)
This study analyzes the implementation of Islamic Religious Education (PAI) values in the moral development of grade X students at SMA 30 Juz Al Qur’an Serang Banten to overcome moral degradation among students. Using a qualitative approach with in-depth interview techniques, participatory observation, and documentation, the data were analyzed following the Miles and Huberman model. The results show the implementation of Islamic value-based character education requires a holistic approach through the integration of Curriculum 2013 with Core Competencies (KI) 1 and KI 2. Five methods of value cultivation proved effective: contextual role modeling, value-based project-based learning, integrated spiritual habituation, experience-based reflective dialogue, and individualized spiritual counseling. These methods follow the stages of value internalization from knowing, feeling, to acting.The successful cultivation of PAI values requires tripartite collaboration between school, family, and community, with the role of teachers as role models according to the principle of “ing ngarso sung tulodo”. The research confirmed significant changes in student behavior in consistency of worship, honesty, discipline, and social care. Effective Islamic religious education is not only transferring cognitive knowledge, but forming character through the appreciation and practice of noble Islamic values.